Lithium titanium aluminum phosphate solid electrolyte nano powder material and preparation method thereof
Nanoscale lithium aluminum titanium phosphate powder was prepared by microwave-assisted sol-gel method and PEALD technology, and a gradient oxide coating layer was constructed. This solved the problems of high-temperature sintering and coating layer inhomogeneity in LATP preparation, improved conductivity and interface stability, and promoted the performance and safety of all-solid-state batteries.
Patent Information
- Application Number
- CN202511152788.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-18
- Publication Date
- 2025-12-02
AI Technical Summary
Existing LATP preparation methods suffer from problems such as high sintering temperature leading to lithium volatilization loss, high energy consumption, large grain size, complex traditional sol-gel process, use of toxic organic titanium sources, poor coating uniformity, and high-temperature sintering easily leading to cracking or element interdiffusion.
By combining microwave-assisted sol-gel method with plasma-enhanced atomic layer deposition (PEALD) technology, nano-sized lithium aluminum titanium phosphate powder was prepared and a gradient oxide coating layer was constructed on its surface to achieve nano-sized particles and atomic-level uniformity of the coating layer. Microwave treatment was used to shorten the synthesis time, and PEALD was used to deposit the gradient oxide intermediate layer at low temperature.
The nano-sized, high-purity, and surface gradient oxide-coated LATP powders were achieved, which improved ionic conductivity and interfacial stability, suppressed side reactions, and enhanced the cycle life and safety performance of all-solid-state batteries.
Abstract
Description
Technical Field
[0001] This invention relates to the technical field of solid electrolytes, and more particularly to a lithium titanium aluminum phosphate solid electrolyte nanopowder material and its preparation method. Background Technology
[0002] Lithium titanium aluminum phosphate (Li 1+x Al x Ti 2-x (PO4)3, LATP, is a solid electrolyte material with a NASICON structure. Due to its high ionic conductivity, good chemical stability, and thermal stability, it has broad application prospects in all-solid-state lithium-ion batteries. However, the preparation of LATP still faces many challenges. While the traditional solid-state sintering method is simple, the high sintering temperature (typically >1000℃) easily leads to lithium volatilization and loss, resulting in low product purity, large grain size (>1μm), requiring additional ball milling, high energy consumption, and easy introduction of impurities. The sol-gel method, although enabling lower-temperature synthesis, is complex, time-consuming, and often uses toxic organic titanium sources, which is detrimental to environmental protection and large-scale production. Furthermore, LATP is prone to Ti oxidation when in contact with the lithium metal anode. 4+ Restore to Ti 3+ Side reactions can occur, affecting battery performance. To address this issue, existing technologies attempt to suppress side reactions by coating the surface with oxides (such as Al2O3 and ZnO). However, the coating layer suffers from poor uniformity and uncontrollable thickness, and high-temperature sintering easily leads to cracking of the coating layer or interdiffusion of elements with the substrate. Therefore, developing an efficient, environmentally friendly, and controllable method for preparing and modifying LATP remains an important direction in current solid-state electrolyte research. Summary of the Invention
[0003] In view of the shortcomings of the prior art, this invention provides a method for preparing lithium aluminum titanium phosphate (LATP) solid electrolyte nanopowder materials to solve the problems of lithium volatilization loss, high energy consumption, large grain size (>1μm), and the need for additional ball milling in traditional solid-state sintering methods due to excessively high sintering temperatures (>1000℃), as well as the problems of complex processes, use of toxic organic titanium sources, long drying / calcination cycles (>24h), and difficulty in large-scale production in traditional sol-gel methods. Furthermore, this invention aims to solve the problems of poor coating uniformity, uncontrollable thickness, and easy cracking or elemental interdiffusion between the coating layer and the matrix caused by high-temperature sintering in existing coating technologies. By innovatively combining microwave-assisted sol-gel method with plasma-enhanced atomic layer deposition (PEALD) technology, this invention achieves nano-sized, high-purity LATP powder and atomically uniform deposition of surface gradient oxide coating layers, thereby significantly improving the ionic conductivity, interfacial stability, and cycle life of the material, providing key material support for high-performance all-solid-state lithium-ion batteries.
[0004] To achieve the above objectives, the technical solution adopted by the present invention is as follows: A method for preparing lithium aluminum titanium phosphate solid electrolyte nanopowder material, the method comprising the following steps: S1: Weigh lithium, aluminum, titanium, and phosphorus sources according to the specified ratio, dissolve them in deionized water to form a mixed solution, add a complexing agent, and adjust the pH to 7-9 to obtain a sol precursor. Step S1, by precisely controlling the raw material ratio and using a complexing agent, achieves uniform mixing of lithium, aluminum, titanium, and phosphorus elements at the molecular level, solving the problems of uneven mixing and easy segregation of raw materials in traditional solid-phase methods. Simultaneously, adjusting the pH to 7-9 promotes sol formation, providing a good precursor structure basis for subsequent microwave processing and gelation, thus helping to obtain nano-lithium aluminum titanium phosphate powder with uniform particle size and high purity.
[0005] S2: The sol precursor obtained in step S1 is placed in a microwave reactor for microwave treatment to obtain a gel-like intermediate. Step S2 utilizes the rapid and uniform characteristics of microwave heating, significantly shortening the drying and gelation time required in the traditional sol-gel method, and avoiding the problems of lithium volatilization and excessive grain growth caused by prolonged high-temperature treatment. Microwave treatment can also promote the full reaction and structural reorganization of the components in the precursor, forming a dense and uniform gel-like intermediate, providing a good structural basis for subsequent annealing.
[0006] S3: After grinding the intermediate obtained in step S2, annealing is performed in an inert atmosphere to obtain nano-sized lithium aluminum titanium phosphate powder with a primary particle size of 80-120 nm. Step S3, through grinding and annealing in an inert atmosphere, further promotes uniform grain growth and perfects the crystal phase, avoiding lithium volatilization and impurity phase formation during high-temperature sintering. The resulting powder has a particle size controlled within the range of 80-120 nm, possessing a large specific surface area and good dispersibility, which is beneficial for improving the ionic conductivity of the material and the uniformity of subsequent coating processes.
[0007] S4: The nano-sized lithium aluminum titanium phosphate powder obtained in step S3 is placed in a plasma-enhanced atomic layer deposition (PEALD) reaction chamber, evacuated to ≤1 Pa, and a plasma activation gas is introduced. Trimethylaluminum (TMA) and titanium tetrachloride (TiCl4) precursors are alternately pulsed, controlling the Al / Ti pulse ratio to 3:1 to 1:3, to deposit a gradient oxide intermediate layer. Step S4 uses PEALD technology to perform surface activation treatment on the nano-sized LATP powder at low temperature (≤200℃), solving the problem of damage to the LATP crystal structure caused by traditional high-temperature coating methods. The plasma activation gas (such as an argon / oxygen mixture) can effectively clean the powder surface and introduce active sites, providing good interface conditions for the subsequent uniform deposition of the gradient oxide coating layer. Simultaneously, step S4 achieves atomic-level precise deposition of a gradient oxide intermediate layer from aluminum-rich (Al2O3) to titanium-rich (TiO2) by precisely controlling the pulse ratio and cycle number of the TMA and TiCl4 precursors. This gradient structure not only enhances the bonding force between the coating layer and the LATP matrix, but also effectively alleviates the lattice mismatch problem, improving the structural and chemical stability of the coating layer.
[0008] S5: Oxygen plasma is introduced to oxidize the residual precursor, forming an Al2O3@Al2TiO5@TiO2 gradient oxide coating layer with a thickness of 0.5–2 nm. Step S5 uses oxygen plasma treatment to completely oxidize the residual organic precursor, forming a dense, pinhole-free gradient oxide coating layer. The thickness of this coating layer is precisely controlled within the range of 0.5–2 nm, which effectively isolates the direct contact between LATP and the lithium metal anode, suppressing the occurrence of side reactions, and maintaining a low interfacial impedance, which is conducive to the rapid transport of lithium ions.
[0009] S6: Annealing at 150–200°C for 30–60 min in an inert atmosphere stabilizes the coating layer structure, ultimately yielding the lithium titanium aluminum phosphate solid electrolyte nanopowder material. Step S6, through low-temperature annealing, further stabilizes the crystal structure and chemical composition of the gradient oxide coating layer, eliminating stress defects that may occur during deposition. The use of an inert atmosphere (such as nitrogen or argon) avoids the impact of high-temperature oxidation on the LATP matrix, ensuring the structural integrity and performance stability of the final material, thereby obtaining a lithium titanium aluminum phosphate solid electrolyte nanopowder material with high ionic conductivity, excellent interfacial stability, and long cycle life.
[0010] As a preferred technical solution, in step S1, the lithium source is selected from lithium carbonate, lithium hydroxide or lithium acetate; the aluminum source is aluminum nitrate; the titanium source is anatase titanium dioxide; and the phosphorus source is ammonium dihydrogen phosphate.
[0011] As a preferred technical solution, in step S1, the lithium source, aluminum source, titanium source and phosphorus source are weighed according to the stoichiometric ratio Li:Al:Ti:P=(1+x):x:(2-x):3; wherein, 0<x≤0.5.
[0012] As a preferred technical solution, in step S1, the complexing agent is at least one of citric acid, tartaric acid, and ethylenediaminetetraacetic acid.
[0013] As a preferred technical solution, in step S2, the power of the microwave reactor is 500-1000W and the frequency is 2.45GHz; the temperature of the microwave treatment is 600-800℃ and the time is 2-4h.
[0014] As a preferred technical solution, in step S3, the annealing treatment is carried out at a temperature of 500-700°C for 1-2 hours, and the inert atmosphere is nitrogen or argon.
[0015] As a preferred technical solution, in step S4, the plasma activation gas is a mixture of argon and oxygen.
[0016] As a preferred technical solution, in step S4, the plasma activation gas is a mixture of argon and oxygen.
[0017] The deposition temperature of the plasma-enhanced atomic layer deposition is ≤200℃.
[0018] As a preferred technical solution, in step S4, the alternating pulse cycle is performed 10 to 30 times.
[0019] Another aspect of the present invention is to provide a lithium titanium aluminum phosphate solid electrolyte nanopowder material, which is prepared by the preparation method of the lithium titanium aluminum phosphate solid electrolyte nanopowder material described above.
[0020] The beneficial effects of this invention are: This invention discloses a method for preparing lithium aluminum titanium phosphate (LATP) solid electrolyte nanoparticles. Based on the innovative microwave-assisted sol-gel method for synthesizing LATP nanoparticles, this method combines plasma-enhanced atomic layer deposition (PEALD) technology to construct a gradient oxide coating layer (Al₂O₃@Al₂TiO₅@TiO₂) on the LATP surface. This not only achieves nano-sized LATP powder (80–120 nm) and high purity, but also realizes atomic-level uniformity and a gradient structure in the surface coating layer. This design not only enhances the interfacial stability between LATP and the lithium metal anode, but also effectively suppresses the degradation of TiO₂. 4+ To Ti 3+ The reduction side reaction also maintains the high ionic conductivity of LATP itself (≥1.2×10⁻⁶). -4S / cm helps improve the cycle life and safety performance of all-solid-state batteries.
[0021] In summary, the lithium titanium aluminum phosphate solid electrolyte nanopowder material of the present invention not only has excellent electrochemical performance, thermal stability and mechanical strength, but also has a green and environmentally friendly preparation process, low energy consumption and easy large-scale production, which can meet the long-term durability and stability requirements of solid electrolyte materials for high-performance all-solid-state lithium-ion batteries. Detailed Implementation
[0022] The following description is intended to disclose the invention and enable those skilled in the art to implement it. The preferred embodiments described below are merely examples, and other obvious variations will occur to those skilled in the art.
[0023] Example 1: The preparation method of lithium titanium aluminum phosphate solid electrolyte nanopowder material in this example includes the following steps: S1: Weigh out 5g of lithium hydroxide, 12.5g of aluminum nitrate, 8g of anatase titanium dioxide, and 10g of ammonium dihydrogen phosphate according to the proportions, dissolve them separately in 150mL of deionized water, stir until completely dissolved, mix them together, add 3g of citric acid as a complexing agent, continue stirring for 30min, adjust the pH to 7.8 with 10wt% ammonia water, and obtain a clear and transparent sol precursor.
[0024] S2: The above sol precursor was transferred to a microwave reactor, the microwave power was set to 700W and the frequency to 2.45GHz, and the mixture was microwaved at 750℃ for 3h. Stirring was maintained during the reaction. After the treatment was completed, the mixture was naturally cooled to room temperature to obtain a dense and uniform gel intermediate.
[0025] S3: Take out the gel-like intermediate, grind it in an agate mortar for 30 minutes to obtain fine powder, then place it in a tube furnace, heat it to 550℃ at 5℃ / min under an argon atmosphere, hold it for 1.5 hours, and after annealing, let it cool naturally to room temperature to obtain nano-lithium titanium aluminum phosphate powder with a primary particle size of 80-120nm.
[0026] S4: The nano-sized lithium aluminum titanium phosphate powder was uniformly spread on the sample stage of the plasma enhanced atomic layer deposition (PEALD) reaction chamber. The vacuum was evacuated to 0.5 Pa, and an argon / oxygen mixture (volume ratio 4:1) was introduced as the plasma activation gas. The plasma power was set to 150 W. Trimethylaluminum (TMA) and titanium tetrachloride (TiCl4) precursors were alternately pulsed, and the Al / Ti pulse ratio was gradually changed from 3:1 to 1:3 for a total of 20 cycles. The deposition temperature was 180 °C, the pulse time was 0.1 s, and the pulse interval was purged with argon for 10 s to obtain a gradient oxide intermediate layer.
[0027] S5: After deposition, oxygen plasma is continued to be introduced at a power of 200W for 5 minutes to completely oxidize the residual organic precursor and form an Al2O3@Al2TiO5@TiO2 gradient oxide coating layer with a thickness of 1.0±0.2nm.
[0028] S6: The coated powder is placed in a tube furnace and heated to 160°C at 5°C / min under an argon atmosphere. The temperature is held for 45 min and then naturally cooled to room temperature after annealing to obtain a stable and dense coated lithium aluminum titanium phosphate solid electrolyte nanopowder material.
[0029] Performance test results show that the obtained lithium aluminum titanium phosphate solid electrolyte nanoparticle material has a uniform particle size distribution, with primary particle sizes concentrated in the range of 80–120 nm and a specific surface area of 15.2 m². 2 / g. X-ray diffraction (XRD) analysis showed that the material has good crystallinity and is free of impurity phases. The ionic conductivity was measured to be 1.3 × 10⁻⁶ g. -4 Compared to uncoated lithium aluminum titanium phosphate powder, the ionic conductivity is improved by approximately 20% (S / cm). In all-solid-state batteries assembled with lithium metal anodes, this material exhibits excellent interfacial stability, with a capacity retention of 92.5% and an average coulombic efficiency of 99.8% after 1000 cycles at 0.5C.
[0030] Example 2: The preparation method of lithium titanium aluminum phosphate solid electrolyte nanopowder material in this example includes the following steps: S1: Weigh out 15.5g of lithium carbonate, 12.5g of aluminum nitrate, 8g of anatase titanium dioxide, and 110g of ammonium dihydrogen phosphate according to the proportions, dissolve them separately in 150mL of deionized water, stir until completely dissolved, mix them together, add 3.5g of tartaric acid as a complexing agent, continue stirring for 30min, adjust the pH to 7.5 with 10wt% ammonia water, and obtain a clear and transparent sol precursor.
[0031] S2: The above sol precursor was transferred to a microwave reactor, the microwave power was set to 800W and the frequency to 2.45GHz, and the mixture was microwaved at 700℃ for 3h. Stirring was maintained during the reaction. After the treatment was completed, the mixture was naturally cooled to room temperature to obtain a dense and uniform gel intermediate.
[0032] S3: Take out the gel-like intermediate, grind it in an agate mortar for 30 minutes to obtain fine powder, then place it in a tube furnace, heat it to 600℃ at 5℃ / min under an argon atmosphere, hold it for 1.5 hours, and after annealing, let it cool naturally to room temperature to obtain nano-lithium titanium aluminum phosphate powder with a primary particle size of 80-120nm.
[0033] S4: The nano-sized lithium aluminum titanium phosphate powder was uniformly spread on the sample stage of the plasma enhanced atomic layer deposition (PEALD) reaction chamber. The vacuum was evacuated to 0.5 Pa, and an argon / oxygen mixture (volume ratio 4:1) was introduced as the plasma activation gas. The plasma power was set to 150 W. Trimethylaluminum (TMA) and titanium tetrachloride (TiCl4) precursors were alternately pulsed, and the Al / Ti pulse ratio was gradually changed from 3:1 to 1:3 for a total of 20 cycles. The deposition temperature was 190 °C, the pulse duration was 0.1 s, and the pulse interval was purged with argon for 10 s to obtain a gradient oxide intermediate layer.
[0034] S5: After deposition, oxygen plasma is continued to be introduced at a power of 200W for 5 minutes to completely oxidize the residual organic precursor and form an Al2O3@Al2TiO5@TiO2 gradient oxide coating layer with a thickness of 1.0±0.2nm.
[0035] S6: The coated powder is placed in a tube furnace and heated to 180°C at 5°C / min under an argon atmosphere. The temperature is held for 45 min and then naturally cooled to room temperature after annealing to obtain a stable and dense coated lithium aluminum titanium phosphate solid electrolyte nanopowder material.
[0036] Performance test results show that the primary particle size of the obtained lithium aluminum titanium phosphate solid electrolyte nanoparticle material is in the range of 80–120 nm, with a relatively concentrated particle size distribution and a specific surface area of 14.8 m². 2 / g. XRD analysis showed that the material had good crystallinity and no obvious impurity phases. The ionic conductivity was 1.25 × 10⁻⁶ g. -4 The S / cm ratio is approximately 18% higher than that of uncoated lithium titanium aluminum phosphate powder. In all-solid-state battery testing, when this material is in contact with a lithium metal anode, the battery retains 91.8% of its capacity after 1000 cycles at 0.5C rate, with an average coulombic efficiency of 99.7%.
[0037] Example 3: The preparation method of lithium titanium aluminum phosphate solid electrolyte nanopowder material in this example includes the following steps: S1: Weigh 14g of lithium acetate, 12.5g of aluminum nitrate, 8g of anatase titanium dioxide, and 10g of ammonium dihydrogen phosphate according to the proportions, dissolve them separately in 150mL of deionized water, stir until completely dissolved, mix them, add 4g of ethylenediaminetetraacetic acid as a complexing agent, continue stirring for 30min, adjust the pH to 8.3 with 10wt% ammonia water, and obtain a clear and transparent sol precursor.
[0038] S2: The above sol precursor was transferred to a microwave reactor, the microwave power was set to 900W and the frequency to 2.45GHz, and the mixture was microwaved at 650℃ for 4h. Stirring was maintained during the reaction. After the treatment was completed, the mixture was naturally cooled to room temperature to obtain a dense and uniform gel intermediate.
[0039] S3: Take out the gel-like intermediate, grind it in an agate mortar for 30 minutes to obtain fine powder, then place it in a tube furnace, heat it to 650℃ at 5℃ / min under an argon atmosphere, hold it for 1.5h, and after annealing, let it cool naturally to room temperature to obtain nano-lithium titanium aluminum phosphate powder with a primary particle size of 80-120nm.
[0040] S4: The nano-sized lithium aluminum titanium phosphate powder was uniformly spread on the sample stage of the plasma enhanced atomic layer deposition (PEALD) reaction chamber. The vacuum was evacuated to 0.5 Pa, and an argon / oxygen mixture (volume ratio 4:1) was introduced as the plasma activation gas. The plasma power was set to 150 W. Trimethylaluminum (TMA) and titanium tetrachloride (TiCl4) precursors were alternately pulsed, and the Al / Ti pulse ratio was gradually changed from 3:1 to 1:3 for a total of 20 cycles. The deposition temperature was 200 °C, the pulse time was 0.1 s, and the pulse interval was purged with argon for 10 s to obtain a gradient oxide intermediate layer.
[0041] S5: After deposition, oxygen plasma is continued to be introduced at a power of 250W for 5 minutes to completely oxidize the residual organic precursor and form an Al2O3@Al2TiO5@TiO2 gradient oxide coating layer with a thickness of 1.0±0.2nm.
[0042] S6: The coated powder is placed in a tube furnace and heated to 200°C at 5°C / min under an argon atmosphere. The temperature is held for 60 min and then naturally cooled to room temperature after annealing to obtain a stable and dense coated lithium aluminum titanium phosphate solid electrolyte nanopowder material.
[0043] Performance test results show that the obtained lithium aluminum titanium phosphate solid electrolyte nanoparticle material has a uniform particle size distribution, with primary particle size ranging from 80 to 120 nm and a specific surface area of 14.5 m². 2 / g. XRD analysis showed that the material has high purity and good crystallinity. The ionic conductivity test result was 1.28×10⁻⁶. -4 The S / cm ratio is approximately 19% higher than that of uncoated lithium titanium aluminum phosphate powder. In all-solid-state battery testing, the material exhibits good interfacial stability, with a capacity retention of 92.0% and an average coulombic efficiency of 99.7% after 1000 cycles at 0.5C.
[0044] The foregoing has shown and described the basic principles, main features, and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The embodiments and descriptions in the specification are merely principles of the invention. Various changes and modifications can be made to the invention without departing from its spirit and scope, and all such changes and modifications fall within the scope of the claimed invention.
Claims
1. A method for preparing lithium titanium aluminum phosphate solid electrolyte nanopowder material, characterized in that, The preparation method includes the following steps: S1: Weigh out lithium source, aluminum source, titanium source and phosphorus source in proportion, dissolve in deionized water to form a mixed solution, add complexing agent, adjust pH to 7-9, and obtain sol precursor; S2: The sol precursor obtained in step S1 is placed in a microwave reactor for microwave treatment to obtain a gel-like intermediate. S3: After grinding the intermediate obtained in step S2, anneal it in an inert atmosphere to obtain nano-lithium titanium aluminum phosphate powder with a primary particle size of 80-120 nm. S4: Place the nano-lithium aluminum titanium phosphate powder obtained in step S3 into the plasma-enhanced atomic layer deposition reaction chamber, evacuate to ≤1Pa, and introduce plasma activation gas; alternately pulse trimethylaluminum and titanium tetrachloride precursors, control the Al / Ti pulse ratio to 3:1 to 1:3, and deposit a gradient oxide intermediate layer. S5: Introducing oxygen plasma to oxidize the residual precursor, forming an Al2O3@Al2TiO5@TiO2 gradient oxide coating layer with a thickness of 0.5-2nm; S6: Annealing at 150-200℃ for 30-60 minutes in an inert atmosphere to stabilize the coating structure, finally obtaining the lithium titanium aluminum phosphate solid electrolyte nanopowder material.
2. The preparation method of lithium titanium aluminum phosphate solid electrolyte nanopowder material as described in claim 1, characterized in that, In step S1, the lithium source is selected from lithium carbonate, lithium hydroxide, or lithium acetate; the aluminum source is aluminum nitrate; the titanium source is anatase titanium dioxide; and the phosphorus source is ammonium dihydrogen phosphate.
3. The preparation method of lithium titanium aluminum phosphate solid electrolyte nanopowder material as described in claim 1, characterized in that, In step S1, the lithium source, aluminum source, titanium source and phosphorus source are weighed according to the stoichiometric ratio Li:Al:Ti:P=(1+x):x:(2-x):3; wherein, 0<x≤0.
5.
4. The preparation method of lithium aluminum titanium phosphate solid electrolyte nanopowder material as described in claim 1, characterized in that, In step S1, the complexing agent is at least one of citric acid, tartaric acid, and ethylenediaminetetraacetic acid.
5. The preparation method of lithium titanium aluminum phosphate solid electrolyte nanopowder material as described in claim 1, characterized in that, In step S2, the power of the microwave reactor is 500-1000W and the frequency is 2.45GHz; the temperature of the microwave treatment is 600-800℃ and the time is 2-4h.
6. The method for preparing lithium aluminum titanium phosphate solid electrolyte nanopowder material as described in claim 1, characterized in that, In step S3, the annealing process is carried out at a temperature of 500–700°C for 1–2 hours, and the inert atmosphere is nitrogen or argon.
7. The preparation method of lithium aluminum titanium phosphate solid electrolyte nanopowder material as described in claim 1, characterized in that, In step S4, the plasma activation gas is a mixture of argon and oxygen.
8. The method for preparing lithium aluminum titanium phosphate solid electrolyte nanopowder material as described in claim 1, characterized in that, In step S4, the deposition temperature of the plasma-enhanced atomic layer deposition is ≤200℃.
9. The method for preparing lithium aluminum titanium phosphate solid electrolyte nanopowder material as described in claim 1, characterized in that, In step S4, the alternating pulse cycle is repeated 10 to 30 times.
10. A lithium titanium aluminum phosphate solid electrolyte nanopowder material, characterized in that, The lithium titanium aluminum phosphate solid electrolyte nanopowder material is prepared by the preparation method of lithium titanium aluminum phosphate solid electrolyte nanopowder material as described in any one of claims 1 to 9.
Citation Information
Cited By
Continuous low temperature plasma fluidized bed coating process and system for aluminum lithium alloy powders
CN122480323A